"FU": One Response to the Liminal State Immigrant Youth Must Navigate. (29th January 2019) - Rodriguez, Darlene Xiomara; McDaniel, Paul N.; Bisio, Gianni
Abstract : Undocumented youth experience partial integration in some institutional spaces but remain barred from others. Although they are permitted to attend and graduate from K–12 public schools, the geographic unevenness of immigration policy leads to inequitable access to higher education for undocumented youth. In this article, we examine undocumented higher education access and how an underground freedom school is providing an alternative. We apply the theoretical lens of spaces of care within the framework of geographies of care to understand the uneven legal geographies that exist and the structures that emerge to equip and empower youth to leverage their experiences with illegality.